Understanding conflicting rationalities in city planning: a case study of co-produced infrastructure in informal settlements in Kampala - Siame, Gilbert (School of Architecture, Planning and Geomatics, 2017)
Kampala is Uganda's capital city and is one the fastest growing cities in the world. Over 60% of the city's urban population live and work informally. In 2002, the Ugandan Minister of Lands, Housing and Urban Development attended the World Urban Forum in Kenya, where he met with the international president of Slum/Shack Dwellers International (SDI), Jockin Arputham. The Minister requested the support of SDI to mobilise the residents of Kampala for settlement upgrading. Following this invitation, the SDI president, with Federation members from South Africa and India, visited Kampala. This visit resulted in the signing of an agreement to enable community residents and the state to jointly improve the living conditions of people in informal settlements in Kampala. This marked the beginning of a new form of state-society relations, called co-production. These relations have grown, evolved and progressively matured over the years. This evolutionary case study asks how co-production engagements in the City of Kampala provide empirical support for an enhanced theoretical framework in planning which contributes to ideas of state-society engagement in the cities of the global South. Drawing on poststructuralist theory and cases of co-production, a conceptual framework provides the theoretical basis to examine how service delivery and city planning under co-production are shaped by power and rationalities that occur at the interface between state and society. This study draws on key proponents of the case study method. Primary data and information were collected, using semi-structured interviews. Document analysis and observations were used to supplement the interview processes and data. The findings were analysed and then used to engage with the theoretical materials in order to write back to theory and then generate theoretical prepositions on planning theory and co-production as an interventive planning framework. Key findings show that communities and civic groups used tools of enumerations, exchange visits and savings to assert their claims and demands, as well as to advance and secure their survival assets and systems. The study reveals complex multifaceted and dynamic power struggles and matrixes within and between structures of the state in the implementation of various co-production initiatives and relations. The state displays and relies on incoherent legal and policy positions, acts informally and operates between old and new ways of engaging with communities. The study further reveals tension points, reversals and the 'holding back' of state power during encounters of state, networked and multiple community power bases that have strong and influential claims to urban space, materialities such as land, trading spaces, informal livelihood systems, place and belonging. The narratives show that community is segmented and conflicted, with individuals and civic groups straddling the divide between state and societal spaces. The combination of organised community resistance and collaboration led to 'quiet encroachment' to shift state positions on development regulations and to disrupt and refine states' schemes of community intervention to become open and more inclusive. The conflicting rationalities and deep differences between state agents and communities extend beyond the binary of state and 'community'. The narratives reveal the fragmented nature of the state - formal and informal - and the divisions within and between society and civic groups characterised by the politics of control of space and territoriality, differentiation and belonging. The case study engages with theory to provide an important caution against the limitations of assuming that planning can adopt consensualist processes in the cities of the South. It suggests that co-production offers a more productive and realistic way of approaching state-society engagement in planning, but is also fraught with difficulties that are also present in the wider context within which engagement occurs. Therefore, this thesis also argues that planning in the South should be seen as both a collaborative and conflicted process. In addition, it postulates that there is nothing peaceful about urban life, and that power and conflict are ubiquitous elements that both produce and are a product of the interface between state and society.